The impacts of biofuels production in rural Kansas: local perceptions - Iaroi, Albert (Kansas State University, 2013)
This dissertation examines the discourse of biofuels development in Kansas as promoted by rural growth machines. Corn-based ethanol production capacity and use in the United States has grown exponentially between 2000 and 2009, culminating with the 2007 Energy Independence and Security Act’s 36 billion gallon Renewable Fuels Standard 2. At the national level, biofuels development is promoted by the media as important to national goals such as energy/national security, economic growth, and environmental improvement. Examination of the biofuels discourse employed content analysis of newspaper articles as well as in-depth individual interviews and focus groups. The analysis revealed that rural growth machines created an ethanol discourse similar to the one promoted at national level, but with an almost exclusive emphasis on the economic development frame. The rural growth machine’s ideological hegemony promoting ethanol development in the region was maintained through their power of creating and disseminating information. For the issue of biofuels development in Kansas, the analyzed newspapers played both conduit and contributor roles, as newspaper coverage strongly supported the interests of growth machines when the subject was local economic growth opportunities. Members of the rural growth machines set an exclusive and one-sided discourse to legitimate their pro-growth activities and to portray the ethanol development projects as corresponding with the wider good of these communities. Because of dwindling demographic and economic bases as well as scarce natural resources, local political and economic elites approached the issue of growth form a standpoint of hegemony. They promoted growth to carry out their own political and economic agenda while there was a strong desire among the residents for almost any type of economic development. This might explain the weak opposition to the actions of the growth machine in these rural settings.
Keywords: Biofuels; Rural; Growth machine; Sociology (0626)